Anisotropic virtual gain and large tuning of particles’ scattering by complex-frequency excitations - G. P. Zouros; I. Loulas; E. Almpanis; A. Krasnok; K. L. Tsakmakidis (Communications Physics (Nature Publishing Group), 2024)
Active tuning of the scattering of particles and metasurfaces is a highly sought-after property for a host of electromagnetic and photonic applications, but it normally requires challenging-to-control tunable (reconfigurable) or active (gain) media. Here, we introduce the concepts of anisotropic virtual gain and oblique Kerker effect, where a completely lossy anisotropic medium behaves exactly as its anisotropic gain counterpart upon excitation by a synthetic complex-frequency wave. The strategy allows one to largely tune the magnitude and angle of a particle’s scattering simply by changing the shape (envelope) of the incoming radiation, rather than by an involved medium-tuning mechanism. The so-attained anisotropic virtual gain enables directional super-scattering at an oblique direction with fine-management of the scattering angle. Our study is based on analytical techniques that allow multipolar decomposition of the scattered field in agreement with full-wave simulations, and lays the foundations for a light management method.